Perancangan Alat Monitoring Pendeteksi Suara di Ruangan Bayi RS Vita Insani Berbasis Arduino Menggunakan Buzzer - Handri Al Fani; Sumarno Sumarno; Jalaluddin Jalaluddin; Dedy Hartama; Indra Gunawan (STMIK Budi Darma, 2020)
Mining age and technology have led to the emergence of an innovation that can help facilitate human activities, especially for parents in controlling and looking after babies. By implementing a sound monitoring system in the baby room based on the Arduino Atmega 328 microcontroller which functions to detect noise. Data from the voice sensor is processed by Arduino via a pin. So Arduino will give instructions to Buzzer to send alarm notifications